(untitled) (Research, Society and Development, 2017)
This work, we evaluate the productive agglomerations of Information Technology in the Metropolitan areas of Curitiba, Londrina, and Maringá, following the peculiarities of the NSI (National System of Innovation) in its approach to the meso economic level. Cooperative relations between companies were analyzed, taking into account organizations and institutions along with supplier-buyers, and the formation of their technical capabilities through relations with support & coordination entities and associations. We conclude that these relations tend to generate positive externalities between region-companies (external economies), both incidental (unconscious) and planned (forged by these companies), which happen due to the geographical closeness of their industrial specializations.